Space Utiliztion and Behaviours of Sumatran Slow Loris (Nycticebus Coucang Boddaert, 1785) in Pematang Siantar Zoo - Mega W. A. Sinaga; Burhanuddin Masyud (Media Konservasi, 2017)
Ex-situ conservation is important for animal conservation, one of kind of conservation organization is zoo. One of the factor who must be consider by conservation organization is cage management. The kind of wildlife species who need to be conserve in ex-situ conservation is Sumatran slow loris (Nycticebus coucang). This species listed as endangered by IUCN Redlist. The aims of this study are to assessspace utilization and behavioral of sumatran slow loris in Pematang Siantar Zoo. The method was used are direct observation, interview and focal animal sampling. The higher percentage of male sumatran slow loris behavior is self active behavior, while female sumatran slow loris is sleep behavior. The higher space utilization by male sumatran slow loris in zone top 1, while female zone 2 top. Keywords: behaviours, Nycticebus coucang, room utilization